Digital Marketing for Entrepreneurs: A Social Network Analysis - Anand Bharathi S; Dr S Rajamohan (Srusti Management Review, 2025)
The evolving landscape of digital marketing has brought forth unprecedented opportunities and formidable challenges for entrepreneurs. This research explores the evolution of digital marketing and entrepreneurship within academic scholarship for the years 2012 to 2023, examining changes in scholarship productivity, authorship, institutional contribution, and impact metrics. The productivity pattern observed reveals a modest beginning in 2012, a dip in 2013, and gradual growth until a peak in 2017, followed by a dramatic increase in 2023, likely due to expanded funding and emerging themes for research. The analysis indicates a rich diversity of contributions across regions and institutions and highlights India as a dominant contributor to the research output. Core topics like digital marketing, entrepreneurship, and SMEs continue to dominate the discourse, while new focus areas like social responsibility and social media indicate shifting focal priorities. Evaluation of prolific authors suggested varied levels of participation, which imply differing degrees of collaboration and consistent input from a single-authored perspective. This reinforces the interdisciplinary character of the researched phenomena, which invite attention from the fields of business, social sciences, and arts and humanities. This summary serves as a basis for formulating further avenues of inquiry within the discipline.